If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(k+4)=(3k-6)
We move all terms to the left:
(k+4)-((3k-6))=0
We get rid of parentheses
k-((3k-6))+4=0
We calculate terms in parentheses: -((3k-6)), so:We get rid of parentheses
(3k-6)
We get rid of parentheses
3k-6
Back to the equation:
-(3k-6)
k-3k+6+4=0
We add all the numbers together, and all the variables
-2k+10=0
We move all terms containing k to the left, all other terms to the right
-2k=-10
k=-10/-2
k=+5
| 4|3w+1|–7=-17. | | 5j+3=2j+21 | | (1/2)-(10/49x)=(24/49)-(1/14x | | 7u-33u=24 | | 9=r+13 | | 7(x-2)-6=3x+8 | | 75/100=4/x | | 20m-6=15m-5 | | (n)(n)+7=151 | | 5(2x-6)=61 | | 8b+9=17b+6 | | 1=2j≥7 | | 3c+1=4c-9 | | 5x+2=9x+6 | | -10s+8=-6-9s+5 | | 7p=6p-9 | | 7c-10=-10c+7 | | 1+8g=4g-3 | | 4a-12=80 | | -9-4z=-5z | | 4+80x=50 | | 2t=-t+10 | | -9+f=-2f | | x/3+x/18=7/6 | | -2p-3=-3p | | 2p-3=-3p | | -5+3y=4y | | (6x+20)=2x | | -66=6x-1 | | 5r=89 | | 46-8x=—18 | | 6=3nn= |